Oha Mina and the Making of Women’s Religious Agency in Bima, Indonesia - Ang Rijal Anas; Ahmad Fauzan; Ang Rijal Amin; Than Tie Amirah; Miftahur Rahmah (Jurnal Dialog, 2026)
To this day, women are still viewed as a vulnerable group. This stigma renders women’s roles in social, political, and religious life insignificant and leaves them feeling powerless. This patriarchal culture fosters gender-biased societal perspectives and perpetuates women’s subordination. Yet, within religious traditions, women’s roles as key participants in religious rituals cannot be underestimated. For example, in the doa wura bola religious tradition of the Bima community, women hold a crucial role as makers of oha mina. This study aims to explore the relationship between women, religiosity, and the formation of agency in the making of oha mina. This study employs a qualitative approach through interviews and literature review to explore the relationship between women, food, and religiosity from the perspective of Anthony Giddens’ agency theory. The findings of this study indicate that food in Bima society is an expression of religiosity and a means of reconciling local values with Islamic traditions. The doa wura bola tradition involves an equal division of roles and distribution of power between women and men. Furthermore, the practice of making oha mina is the locus where agency is formed and new religious authority is consolidated for women.